2018
DOI: 10.2308/jiar-51990
|View full text |Cite
|
Sign up to set email alerts
|

Directors' and Officers' Legal Liability Insurance and Internal Control Weaknesses

Abstract: Directors' and officers' (D&O) legal liability insurance releases directors and officers from the threat of litigation and personal liability stemming from their decisions on behalf of the corporation. While researchers have examined some of the determinants of internal control weaknesses, it is not clear whether excess D&O coverage motivates managers to weaken the quality of firms' internal controls. This study examines whether excess D&O coverage affects the effectiveness of internal controls. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Empirically, it is reported that US firms are charged more for D&O insurance coverage if they have lower earnings quality or prior accounting restatements (Cao & Narayanamoorthy, 2014). In Taiwan, firms with D&O insurance are positively associated with overinvestment but negatively associated with investment efficiency (Li & Liao, 2014), and D&O insurance increases the likelihood of restating financial statements (Weng, Chen & Chi, 2017), internal control weakness (Chen & Keung, 2018) and the number of key audit matters (KAMs) disclosed by auditors (Lin et al, 2020), and it also weakens the sensitivity of directors' compensation to firm performance (Wang & Chen, 2016). Canadian listed firms with D&O insurance have experienced an increase in the cost of equity and a negative market reaction to increased insurance coverage (Chen, Li & Zou, 2016), increased loan spread (Lin et al, 2013), higher audit fees (Chung et al, 2015), aggressive tax reporting activities (Zeng, 2017) and lower earnings conservatism (Chung & Wynn, 2008), as well as lower announcement period abnormal stock returns during merger and acquisition transactions with significantly higher acquisition premiums but lower post-acquisition business synergies (Lin et al, 2011).…”
Section: Epu and Dando Insurancementioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, it is reported that US firms are charged more for D&O insurance coverage if they have lower earnings quality or prior accounting restatements (Cao & Narayanamoorthy, 2014). In Taiwan, firms with D&O insurance are positively associated with overinvestment but negatively associated with investment efficiency (Li & Liao, 2014), and D&O insurance increases the likelihood of restating financial statements (Weng, Chen & Chi, 2017), internal control weakness (Chen & Keung, 2018) and the number of key audit matters (KAMs) disclosed by auditors (Lin et al, 2020), and it also weakens the sensitivity of directors' compensation to firm performance (Wang & Chen, 2016). Canadian listed firms with D&O insurance have experienced an increase in the cost of equity and a negative market reaction to increased insurance coverage (Chen, Li & Zou, 2016), increased loan spread (Lin et al, 2013), higher audit fees (Chung et al, 2015), aggressive tax reporting activities (Zeng, 2017) and lower earnings conservatism (Chung & Wynn, 2008), as well as lower announcement period abnormal stock returns during merger and acquisition transactions with significantly higher acquisition premiums but lower post-acquisition business synergies (Lin et al, 2011).…”
Section: Epu and Dando Insurancementioning
confidence: 99%
“…Lin, Officer & Zou, 2011;Lin et al, 2013;Chung, Hillegeist & Wynn, 2015), Taiwan (e.g. Chang & Chen, 2018;Chen & Keung, 2018;Lai & Tai, 2019) and in the USA (Donelson, Hopkins & Yust, 2018;Lin et al, 2020). Evidence on D&O insurance from emerging markets would be a valuable addition to the international literature.…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of the literature supports the moral hazard effects associated with D&O insurance. The purchase of D&O insurance may increase the likelihood of internal control weaknesses (Chen and Keung, 2018), encourage aggressive financial and tax reporting policies, resulting in less conservative earnings (Chung and Wynn, 2008), and lead to more frequent financial restatements (Weng et al , 2017) and tax avoidance (Zeng, 2017). Furthermore, D&O insurance has been found to weaken the sensitivity of directors' compensation to firm performance (Wang and Chen, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%